Veterinary anesthesia and analgesia the sixth edition of Lumb and Jones - Grimm, Kurt A.; Lamont, Leigh A.; Love, Lydia; Robertson, Sheilah A.; Schroeder, Carrie A. (Wiley-Blackwell, 2024)
"Veterinary Anesthesia and Analgesia: The Sixth Edition of Lumb and Jones is a fully updated revision to this comprehensive, authoritative reference to all aspects of veterinary anesthesia and pain management. Encompassing both scientific principles and clinical applications, the new edition adds new knowledge, techniques, and discussion of emerging issues throughout. Fourteen new chapters significantly expand the coverage of patient monitoring modalities and nociception and pain, while presenting new information on safety culture, infection prevention and control, biomedical engineering, and point-of-care ultrasound. Logically organized into sections, information on basic principles, pharmacology, specific body systems, and specific species is easy to access. Comparative anesthetic considerations for dogs and cats, horses, ruminants, swine, laboratory animals, free-ranging terrestrial mammals, marine mammals, reptiles, amphibians, fish, and birds are discussed. Chapters are devoted to anesthesia and pain management of common domestic species and patient populations, including updated chapters on local and regional anesthetic and analgesic techniques. A companion website offers video clips of point-of-care ultrasound techniques and pain assessment and scoring. With its unparalleled multidisciplinary approach, Veterinary Anesthesia and Analgesia is a must-own volume for veterinary anesthesia specialists and researchers; specialists in other disciplines, including both small and large animal surgeons; practitioners; and students"--